The Role of Self-Efficacy and Soft Skills in Improving Academic Quality at SMP Negeri 3 Muara Batu - Cut Maulinda Juniar; Muhammad Anggung Manumanoso Prasetyo; Jay Rodel Cadizal Serdenia (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2026)
This research aims to analyze the application of self-ability and soft skills in improving the academic quality of students at SMP Negeri 3 Muara Batu. The research method uses a qualitative approach with a case study type. Research subjects included teachers and students selected using purposive sampling. Data collection techniques were carried out through interviews conducted boldly using WhatsApp to explore the experiences and views of informants. Data was analyzed descriptively to comprehensively understand the ongoing learning process. The research results show that the implementation of self-efficacy is carried out through providing motivation, positive feedback, and opportunities for students to actively participate in learning. This can increase students' self-confidence, perseverance and courage in facing learning challenges. Soft skills development is carried out through collaborative learning such as group discussions, presentations, and cooperation on assignments, which contribute to increasing communication skills, responsibility, and student involvement in the learning process. A conducive school environment also supports improving academic quality through a comfortable learning atmosphere, positive interactions, and directed learning. Thus, implementing self-efficiency, developing soft skills, and supporting the school environment are important factors that are interrelated in improving the quality of students optimally.